Are benzodiazepines effective in treating catatonia?. (January 2021) - Carthy, Elliott
SUMMARY: Establishing an evidence base for the clinical management of catatonia is made difficult by the heterogeneous nature of the condition and the limited understanding of its pathophysiology. Benzodiazepines are a mainstay of treatment. The Cochrane review discussed identified only one eligible study (17 participants with catatonia who received either lorazepam or oxazepam), which found no difference on the single outcome measure (a 50% improvement on a visual analogue scale). This commentary discusses the findings in more detail, and considers what constitutes high-quality evidence for the acute treatment of catatonia, why there is such a paucity of randomised controlled trials (RCTs) on the topic and whether RCTs are both feasible and appropriate for the condition.